Calculation of a conversion factor for estimating the glycolytic contribution in exercise from post-exercise blood lactate concentration - Hill, David W.; Mihalek, John Michael (Frontiers in Physiology, 2024)
Purpose: Often, the glycolytic contribution in a bout of heavy or severe intensity exercise is estimated by multiplying the increase in blood lactate concentration above resting levels that is engendered by the exercise (in mM) by 3.3 (or 3) mL·kg−1 per mM. Our purpose was to verify the value of this conversion factor, using methods that were completely different from those of the original studies. Methods: Six women (mean ± SD), age, 23 ± 1 year; VO2max, 46 ± 4 mL·kg−1·min−1) and three men (23 ± 0 years; 54 ± 8 mL·kg−1·min−1) completed 6 min of heavy intensity exercise in conditions of normoxia and hypoxia (FIO2, ∼12%). VO2 was measured throughout the exercise and 7 min of recovery. The increase in glycolytic contribution was estimated as the reduction in aerobic contribution in hypoxia, after correction for the effects of hypoxia on the oxygen demand and on the contribution from phosphocreatine. The peak post-exercise blood lactate concentration was measured in fingerstick blood samples. Results: The ratio between the increase in estimated glycolytic contribution (in mL·kg–1) in hypoxia and the increase in peak blood lactate concentration (in mM) yielded an oxygen equivalent of 3.4 ± 0.4 mL·kg–1 per mM (range, 2.6 mL·kg−1 per mM to 4.0 mL·kg−1 per mM) for cycle ergometer exercise. Conclusion: These results generally support the use of a common conversion factor to calculate the glycolytic contribution from post-exercise blood lactate concentrations. However, there is some inter-individual variability in the conversion factor.